Perancangan Embedded Web Server Untuk Sistem Monitoring Suhu Dan Kualitas Udder Berbasis Mikrokontroler ATMEGA128 - Sutiana, Aris; Paronda, Abdul Hafid; Sugeng, Sugeng (JREC (Journal of Electrical and Electronics), 2013)
The presence of air quality monitoring in the city was instrumental in the day-to-day humanactivities which serve to have high mobility. As long as there is still no system that can provideaccurate information about the conditions of temperature and air at the site, but this information isneeded as a warning and consideration. Although there are tools needed quite complex because itrequires a computer server, while the use of server computers are found to be efficient when placedat a location outside the room.Based on the above problems the author to design and create a system of temperaturemonitoring and web-based air pollution that can be accessed through the medium of computernetworks. This web-based monitoring systems embedded in a chip, making it more flexible withoutneeding a computer server.Keyword: Embedded Web Server, Temperature Monitoring, Air Quality Monitoring.